Undergraduate Architecture Students’ Perceptions of the Reasons for Their Choice(s) of Profession - Yorgancıoğlu, Derya; Tunalı, Sevinç; ÇETİNEL, MELTEM (Handan Deveci, 2021)
This study aims to analyze the factors, driven by intrinsic and/or extrinsic motivations, that affect the students’ choice(s) of profession before entering the school of architecture and to reveal how the participants’ perceptions of their “self-efficacy” about becoming an architect altered in parallel to the skills they acquire during their professional education. The research, based on the qualitative research methodology, is undertaken in a Bachelor of Architecture degree program in a private university in Istanbul and the data was collected through the participation of 40 undergraduate architecture students from different class levels. The data collection procedures covered four recorded focus group interviews with students at different class levels and the interview transcriptions were analyzed through qualitative content analysis. The results regarding the reasons for studying architecture has revealed that the participants are influenced by (1) their self-perceptions, which overlap with the profession-related qualities and (2) the influence of their social environment and families. It is shown that the professional education that the participants have received has improved their design skills and supported their self-efficacy beliefs in this regard, but made them feel insufficient about technical-practical skills. The research findings have implications for the students who think to study architecture, the secondary education teachers, and the administrators and instructors of schools of architecture for various reasons: by uncovering the interrelated dynamics and requirements of the architectural profession and education, these findings may guide the attempts to choose a profession compatible with individuals’ capabilities and orientations and to structure a balanced architectural curriculum.
Keywords: Architectural Education; Architectural Profession; Design Skill; Profession Choice; Self-efficacy Perception